Therapeutic Potential of Chymase Inhibitors in Cardiovascular Diseases: An Overview - Aga, Qutaiba Ahmed Al Khames; Nair, Anroop B.; Hourani, Wafa; Parasuraman, Subramani; KK, Mueen Ahmed; Sreeharsha, Nagaraja (Indian Journal of Pharmaceutical Education and Research, 2020)
Chymase belongs to the family of serine proteases and is mainly warehoused in a heparin proteoglycan macromolecular complex within the mast cells. Extensive studies have been carried out in the last few decades to assess the role of chymase in human diseases. Recent studies have shown the significance of chymase in blood pressure regulation owing to its efficient angiotensin II forming activity. Angiotensin II-generation routes that are associated with human cardiovascular diseases have pathophysiological importance which is still argumentative. Chymase inhibitors play a distinctive role in regulating the renin-angiotensin system as compared to the inhibitors of angiotensin-converting enzyme and type 1 angiotensin II receptor. Therefore, this mechanism may have a role in medical applications of chymase inhibitors by inactivation of the local renin-angiotensin system to avoid cardiovascular diseases. This review highlights the significant role of chymase inhibitors as a potential approach for the management of cardiovascular diseases such as atherosclerosis, hypertension, vascular proliferation, myocardial infarction and heart failure.
Keywords: Chymase inhibitors; Angiotensin II; Angiotensin-converting enzyme; Mast; cells; Blood pressure regulator; Cardiovascular diseases